What is the content of virtually delivered pain management programmes for people with persistent musculoskeletal pain? A systematic review. Issue 1 (February 2022) - Booth, Gregory; Williams, Deborah; Patel, Hasina; Gilbert, Anthony W
Introduction: Virtual consultations (VC) have been embraced by healthcare organisations during the COVID-19 pandemic. VC allows continuation of patient care while adhering to government advised restrictions and social distancing measures. Multidisciplinary pain management programmes (PMPs) are a core element of many pain services and utilising virtual methods to deliver PMPs has allowed them to continue to provide care. This systematic review aimed to explore the content of existing virtually delivered PMPs and discuss if and how these findings can be used to guide clinical delivery. Methods: Eligible studies included adults (aged ⩾18 years) with persistent musculoskeletal pain and any virtually delivered intervention that was described as a PMP or that had components of PMPs. Databases were searched from inception until July 2020. We performed a content analysis comparing existing interventions with established evidence-based clinical guidelines published by the British Pain Society (BPS). Intervention reporting quality was assessed using the Template for Intervention Description and Replication (TIDieR) checklist: an established checklist developed to improve the completeness of the reporting of interventions. Results: Eight studies were included. One intervention included six of the seven components recommended by the BPS; none included all seven. 'Skills training and activity management' was present in all eight interventions; 'education' and 'cognitive therapy methods' were present in six interventions; 'graded activation' and 'methods to enhance acceptance, mindfulness and psychological flexibility' were present in four interventions; 'physical exercise' was present in two interventions and 'graded exposure' was present in one intervention. None of the studies described all 12 items of the TIDieR checklist adequately enough for replication. Conclusion: Published virtual PMPs partially meet established clinical guidelines. Future virtual PMPs should be based on evidence-based clinical guidelines, and more research is needed to explore the effectiveness of virtually delivered PMPs and each recommended component.